Sistem Informasi Akuntansi (SIA) pada Waroeng Fake - Niswah, Muhlishatun; Putri Mulyana Safira (Indra Institute Research & Publication, 2023)
This research aims to analyze the implementation of the Accounting Information System (AIS) at Waroeng Fake. The research methodology involves literature review, direct observation, and interviews with the management. The findings indicate that the implementation of AIS at Waroeng Fake has enhanced financial management efficiency and inventory control. The conclusion of this research is that AIS plays a crucial role in supporting the effective operations of Waroeng Fake.